Model Kolaborasi antar Stakeholder dalam Menciptakan Pemilu Ramah Lingkungan: Studi Kasus pada Pilkada Serentak DIY 2020 - Sri Sulastri; Laras Lingganingrum; Annisa Risky Ramadan; Tyas Hadi Angesti; Widiyastuti Setiabudi; Ridho Al-Hamdi (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
The holding of elections usually connotes the struggle for office and power but does not pay attention to environmental aspects. Even though the environment is important in survival. Therefore, elections must apply the concept of environmentally friendly elections, however, post-Simultaneous Regional Elections have not reflected environmentally friendly elections but caused visual waste. Therefore, this study aims to find a model of collaboration carried out by stakeholders as an effort to create environmentally friendly elections. The research method used in this study is a qualitative method with a case study approach and analyzed using the Nvivo 12 Plus Qualitative Data Analysis Software. The result of this study is that in the face-to-face process between stakeholders have different roles and do not yet have the same perspective regarding the issue of environmentally friendly elections. Then in building trust between stakeholders there are obstacles in communication, so that it becomes an obstacle to the collaboration process. The conclusion of this study is that the collaboration model run by stakeholders has not been effective and efficient and the collaboration model established is non-formal. Therefore, researchers propose forms of cooperation with formal agreements and collaboration models according to Ansel and Gash (2007) and recommend encouraging the government to issue laws governing Environmentally Friendly Elections and become a reference in the process of organizing campaigns in Indonesia.